2021
DOI: 10.3390/ani11092643
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yellow Wine Lees Supplementation on Milk Antioxidant Capacity and Hematological Parameters in Lactating Cows under Heat Stress

Abstract: Fifteen multiparous lactating Chinese Holstein dairy cows were used in a replicated 3 × 3 Latin Square Design to evaluate the effect of total mixed rations (TMR) containing unfermented and fermented yellow wine lees (YWL) on the oxidative status of heat-stressed lactating cows and the oxidative stability of the milk and milk fatty acids they produced. Cows were fed with three isonitrogenous and isocaloric diets as follows: (1) TMR containing 18% soybean meal, (2) TMR containing 11% unfermented YWL (UM), and (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It has been reported that the substitution of forage and soy protein with high-protein DDG effectively improves feed conversion ratio and milk production in Holstein cows ( Hubbard et al, 2009 ). A recent study reports that feeding cattle with a mixed diet containing yellow wine lees both reduces oxidative stress in heat-stressed cattle and increases the antioxidant capacity of milk ( Yao et al, 2021 ). Another study evaluating the effect of a mixed ration with corn DDGS replacing cornmeal on intake, animal performance, and carcass traits in Nellore cattle demonstrates that DDGS increase average daily gain and carcass gain in cattle ( Da et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the substitution of forage and soy protein with high-protein DDG effectively improves feed conversion ratio and milk production in Holstein cows ( Hubbard et al, 2009 ). A recent study reports that feeding cattle with a mixed diet containing yellow wine lees both reduces oxidative stress in heat-stressed cattle and increases the antioxidant capacity of milk ( Yao et al, 2021 ). Another study evaluating the effect of a mixed ration with corn DDGS replacing cornmeal on intake, animal performance, and carcass traits in Nellore cattle demonstrates that DDGS increase average daily gain and carcass gain in cattle ( Da et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The partial replacement of soybean meal with fermented distillers' grains had a positive effect on feed conversion ratios and improved immune and gut health status in a broiler [8]. Feeding a total mixed ration containing fermented yellow wine lees reduces oxidative stress and improves milk oxidation in heat-stressed cows [9]. These studies indicate that FDG has long-term prospects for feed substitution in the livestock industry.…”
Section: Introductionmentioning
confidence: 79%
“…Feeding dried DGs has been evidenced to improve the growth performance and meat quality of bulls (4). Current studies on the utilization of DDGS as animal feeds focus on the improvement of animal growth performance, weight gain, milk production in dairy cows, meat quality in beef cattle, antioxidant capacity, and stress reduction (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%